2018
DOI: 10.21315/mjms2018.25.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Teleneurosurgery: Outcome of Mild Head Injury Patients Managed in NonNeurosurgical Centre in the State of Johor

Abstract: Background: With teleneurosurgery, more patients with head injury are managed in the primary hospital under the care of general surgical unit. Growing concerns regarding the safety and outcome of these patients are valid and need to be addressed.Method: This study is to evaluate the outcome of patients with mild head injury which were managed in non-neurosurgical centres with the help of teleneurosurgery. The study recruits samples from five primary hospitals utilising teleneurosurgery for neurosurgical consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Above mentioned studies also showed favorable intervention outcomes for the improvement in clinical symptoms, reduction in disease severity and reduction in secondary events facilitated by tele-medicine service. It was also noticed that there was no difference in treatment outcomes to manage mild neurosurgical cases in the non-neurosurgical facility with the help of tele-neurosurgery compared to specialist hospital (Sidek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Above mentioned studies also showed favorable intervention outcomes for the improvement in clinical symptoms, reduction in disease severity and reduction in secondary events facilitated by tele-medicine service. It was also noticed that there was no difference in treatment outcomes to manage mild neurosurgical cases in the non-neurosurgical facility with the help of tele-neurosurgery compared to specialist hospital (Sidek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%